IDIOMS AND PHRASAL VERBS: UNLOCKING NATURAL ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This research provides an extensive academic inquiry into the structural and functional role of multi-word units (MWUs), specifically idioms and phrasal verbs, in achieving linguistic naturalness. The study examines these linguistic phenomena not merely as rhetorical ornaments but as "lexical filters" that distinguish proficient L2 speakers from native-like communicators. It investigates the mechanisms of semantic opacity and syntactic flexibility in reducing communicative friction. The research concludes that the mastery of formulaic language represents the final frontier in achieving absolute communicative competence within the modern global discourse.
Keywords: Idiomaticity, phrasal verbs, formulaic language, semantic opacity, communicative competence, lexical density, L2 acquisition.